(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Diabetic ketoacidosis and Hyperosmolar Hyperglycaemic State are both acute, lifethreatening metabolic complications occurring in patients with Type 1 and Type 2 Diabetes. The presence of both these conditions simultaneously in one patient is always a challenge to the clinicians. We report such a case of a 62-year-old gentleman known to have Type 2 diabetes, presented with multiple episodes of vomiting and collapse. On arrival to the Emergency Department, he was tachycardic and physical examination revealed upper abdominal tenderness. Blood tests revealed initial pH 6.96, HCO3 6.1mmol/L, Glucose high, blood ketones 5.8mmol/L, K 4.5mmol/L, and Lactate 1.7mmol/L. His calculated serum osmolality was 340mmol/Kg, serum amylase 532U/L and Troponin 88ng/ml. He was treated as per the DKA protocol of the trust and was transferred to the High Dependency Unit. In view of his raised serum osmolality, he was diagnosed as having mixed Diabetic Ketoacidosis and Hyperglycaemic Hyperosmolar State. A CT scan of the abdomen was done to find out the underlying etiology which suggested acute pancreatitis. Additionally, he was diagnosed as having Type 2 myocardial infarction (MI). Both the surgical and cardiology teams were involved in his care. Because of his having both DKA and HHS features the management, especially fluid resuscitation was tailored accordingly. Eventually, the patient recovered and was stepped down to the ward 3 days later. Our case emphasizes that prompt and correct diagnosis of diabetic emergencies can lead to successful outcomes in patients with multiple complications as well. Timely diagnosis, thorough clinical and biochemical evaluation, and effective management are essential for the resolution of DKA and HHS. Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 70-72